Global tectonic reconstructions with continuously deforming and evolving rigid plates. (July 2018) - Gurnis, Michael; Yang, Ting; Cannon, John; Turner, Mark; Williams, Simon; Flament, Nicolas; Müller, R. Dietmar
Abstract: Traditional plate reconstruction methodologies do not allow for plate deformation to be considered. Here we present software to construct and visualize global tectonic reconstructions with deforming plates within the context of rigid plates. Both deforming and rigid plates are defined by continuously evolving polygons. The deforming regions are tessellated with triangular meshes such that either strain rate or cumulative strain can be followed. The finite strain history, crustal thickness and stretching factor of points within the deformation zones are tracked as Lagrangian points. Integrating these tools within the interactive platform GPlates enables specialized users to build and refine deforming plate models and integrate them with other models in time and space. We demonstrate the integrated platform with regional reconstructions of Cenozoic western North America, the Mesozoic South American Atlantic margin, and Cenozoic southeast Asia, embedded within global reconstructions, using different data and reconstruction strategies. Highlights: Developed standard procedures to represent regional models of plate deformation. Software is open source and demonstrated with three regional examples. Regional deformation placed in context of global plate motions. Opens pathway to the first global evolving models with plate deformation in deep time.